Navigating Copyright for Libraries : Purpose and Scope. - Coates, Jessica; Owen, Victoria; Reilly, Susan (Berlin/Boston : Walter de Gruyter GmbH, 2022)
The International Federation of Library Associations and Institutions (IFLA) is the leading international body representing the interests of library and information services and their users. It is the global voice of the information profession. The series IFLA Publications deals with many of the means through which libraries, information centres, and information professionals worldwide can formulate their goals, exert their influence as a group, protect their interests, and find solutions to global problems.
Library Applications of Artificial Intelligence -- The Copyright Landscape Affecting TDM Research -- TDM Legislation -- Court-based TDM -- Reforming the Copyright Landscape to Enable Libraries to Support TDM Researchers -- Conclusion -- Acknowledgement -- References -- Contributors.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books